Molecular Profile of the Brazilian Weaver Ant Camponotus textor Forel (Hymenoptera, Formicidae) - Ramalho, M. O. [UNESP]; Martins, C.; Silva, L. M.R. [UNESP]; Martins, V. G. [UNESP]; Bueno, O. C. [UNESP] (Springer Nature, 2016)
Camponotus textor Forel is, to date, the only weaver ant recorded from Brazil, and all existing studies on the species are restricted to describing its weaving and nesting behaviors. The aim of this work is to establish the molecular profile of the species. We sampled eight different colonies by sequencing mitochondrial genes (COI, transfer DNA (tRNA), and an intergenic spacer) and the nuclear gene 28S ribosomal DNA (rDNA). We then assessed haplotype diversity and also analyzed distribution patterns of this species based on the correlation between genetic and geographic distances. Our results provide an additional tool for species identification by identifying new regions that can be used as molecular markers for barcoding (such as the intergenic spacer (IGS) and tRNA-Leu). In addition, the phylogenetic analysis revealed that C. textor has features that could be associated with deep population divergences. We identified a wide range of mitotypes and three distinct groups, suggesting a possible reduction of gene flow between colonies.
Keywords: 28S rDNA; Barcode; Camponotini; phylogeny; systematics